A formação permanente na educação de jovens e adultos: uma sinfonia criada a muitas mãos - Rosa Junior, Mauro Batista da (2023)
By participating in the permanent training of Youth and Adult Education pedagogical assistants in the municipal network of Santo André, focusing on the development of pedagogical work, we were allowed to understand how fragile the collaborative and interdisciplinary action that aims to reach integral education is. Regarding this issue, we elaborated our research question: Based on Freire's theoretical framework, especially the concepts of participation, collaboration and interdisciplinarity, what indications allow us to elaborate a proposal for the permanent training of Pedagogical Assistants? In order to answer this question, based on the thematic investigation methodology as proposed by Paulo Freire (1987), we set up as our main goal to understand which limit-situations are imposed to the development of a collaborative and interdisciplinary work - in the perspective of the Integrated Curriculum - in Santo André’s Youth and Adult Education program. In the perspective of the thematic investigation methodology and based on the assumptions of permanent training, the qualitative research approach enabled us to identify pedagogical assistants’ knowledge from direct experience as well as their limit-situations, desires and intentions, allowing us to propose actions to be developed in articulation with the observed needs. Anchored in the principles of participation, collaboration and interdisciplinarity, at the end of the course, trainer and trainees were involved in the elaboration of an education plan that aimed to overcome their limit-situations, developed from the generative themes unveiled throughout the process. This research has as its main reference the pedagogy of Paulo Freire (1921-1997), given that his contributions are present in all the chapters – from the theoretical basis to the formative compositions. We also brought the work of Ana M. Saul (2018), Alexandre Saul (2015), Antônio F. G. da Silva (2004), Marli E. D. A. de André (1983), Vera M. N. de S. Placco and Vera L. T. A. Souza (2012), among other authors who dialogue with the aforementioned principles